RARRES1 attenuates H2O2-induced RPE cell injury and inhibits choroidal neovascularization - Li, Yimeng; Wang, Caixia; Deng, Tao; Li, Xuejing; Xu, Renhao; Shang, Qingli (Frontiers in Physiology, 2025)
IntroductionNeovascular age-related macular degeneration (nAMD) is a leading cause of vision loss in the elderly, yet its underlying molecular mechanisms remain incompletely understood, and novel biomarkers and therapeutic targets are urgently needed. This study aimed to identify and functionally characterize potential biomarkers and therapeutic candidates for nAMD, with a focus on retinoic acid receptor responder protein 1 (RARRES1). MethodsTandem mass tag (TMT)–based proteomic analysis was performed on aqueous humor samples from patients with nAMD and age-related cataracts. RARRES1 expression was examined in aqueous humor, laser-induced choroidal neovascularization (CNV) model mice, and human ARPE-19 cells exposed to H2O2. Functional studies assessed the effects of RARRES1 on oxidative stress, cell death, inflammatory and angiogenic factor expression, and signaling pathways in ARPE-19 cells. Its effects on proliferation, migration, and tube formation were tested in HUVECs. In vivo, a RARRES1-overexpressing AAV2 vector was injected intraocularly into CNV model mice, and lesion size and vascular leakage were evaluated using fundus fluorescein angiography, hematoxylin and eosin staining, and isolectin B-4 fluorescence staining. ResultsRARRES1 was significantly reduced in the aqueous humor of nAMD patients, in CNV model mice, and in H2O2-treated ARPE-19 cells. Overexpression of RARRES1 in ARPE-19 cells mitigated oxidative stress–induced damage, suppressed inflammatory and angiogenic factor expression, inhibited JNK phosphorylation, and increased Sirtuin 1 and Nrf2 expression. In HUVECs, RARRES1 reduced proliferation, migration, and tube formation. In vivo, intraocular delivery of RARRES1 significantly reduced CNV lesion size and vascular leakage. ConclusionRARRES1 protects retinal pigment epithelial cells from oxidative stress, inhibits choroidal neovascularization, and modulates inflammatory and angiogenic pathways. These findings identify RARRES1 as a potential biomarker and therapeutic target for nAMD.